Fiscal Policy in Open Developing Economies. (International Monetary Fund, 1990)
Based on papers presented at the 44th Congress of the international Institute of Public Finance, this book, edited by Vito Tanzi, deals with public finance and macroeconomic policy in open, developing economies, with case studies of Chile, Mexico, Turkey, Korea, and the Arab oil exporting countries.